Mathematical and metaphysical languages - Leach, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper summarizes some of the ideas that I will present in the book Mathematics and Religion: Our languages of Sign and Symbol, which will be publish by Templeton Press in the month of September 2010. This book is about our languages, but with a focus on the privileged role that mathematics has in our ability to communicate about the world around us. In this sense, mathematics is our «public language». But it is more than that also. As I hope you will see, mathematics leads us through science and brings us to questions about a greater reality, which we call metaphysical reality and which we usually approach in the context of philosophy and religion.
Keywords: signs; symbols; language; formal sciences; empirical sciences; logic; mathematics; metaphysics; religion; theology